On Generating Categories in Theological Ethics: Barth, Genesis and the Ständelehre - Brock, Brian (Tyndale bulletin, 2010)
Though the doctrine of creation is often invoked in Christian ethics, its relation to the book of Genesis remains obscure. The dominance of an ethics of principles among Christian ethicists and exegetes provides one reason for this obscurity in methodologically oversimplifying Scripture in order to make it more accessible for a specific type of modernist ethical methodology. The main emphasis of the article is to investigate the linkages Karl Barth drew between the book of Genesis and the doctrines of Christology and creation in his Church Dogmatics vol. III. While Barth makes important methodological advances on a Christian ethic of principles, his treatment of the doctrine of creation is found to underplay the distinctive thought structures of Genesis 1–4. A brief final section suggests that Luther’s doctrine of the three estates comprehends Barth’s best methodological insights, and in addition, was explicitly formulated as a reading of the biblical text of Genesis. Drawing on the work of Hans Ulrich, I conclude that an updated version of the Ständelehre addresses the systematic problems noted in a Christian ethic of principles and Barth’s doctrine of creation, so yielding a more biblically faithful framework within which a Christian ethic of creation can be developed.